PENDAMPINGAN RANCANGAN TATA ATUR RUANG DAN LANSEKAP DALAM HUNIAN TEMPAT TINGGAL DI KRENDANG, JAKARTA BARAT - Karista, Ardilla Jefri; Fadhilah, Arief; Budiarti, Ratih; Fauzi, Reza (Jurusan Teknik Lingkungan Fakultas Arsitektur Lanskap dan Teknologi Lingkungan, Universitas Trisakti, 2023)
The design of the arrangement needs to be pursued to get the impression of harmony in the residential space. The design of this regulation is also intended to minimize the occurrence of cabin fever for residents during the Covid-19 pandemic. Residential housing for residents of RW 02 Krendang Village is a building in a densely inhabited area where on average the living space is relatively narrow and coincides with one building with another. Residential adaptation was carried out by residents by arranging furniture, but there was a buildup of furniture which resulted in irregularities and an uncomfortable impression. These feelings have the potential to be the cause of cabin fever symptoms. Assistance in Spatial and Landscape Arrangements is intended to increase the understanding of the residents of RW 02 Krendang on the importance of arrangement and regulation in order to achieve a comfortable living space to minimize the occurrence of cabin fever. Implementation of activities through counseling on pilot homes for residents and assistance in designing residential and landscape arrangements for residents who ask about conditions in their respective homes. The success indicators of this Community Service activity will be confirmed and measured through pre-test and post-test. The result of this activity is that residents gain an understanding of the principles of good spatial and landscape management that can be applied in their respective dwellings. The conclusion of this activity is that the residents of RW 02 Krendang Village are paying more attention to the quality of the living space in their respective residences